Analyzing the impact of external debt on capital formation in Nigeria: An autoregressive distributed lag approach - Abdullahi, Muhammad Mustapha; Hassan, Sallahuddin; Abu Bakar, Nor'Aznin (MCSER Publishing, Rome-Italy, 2016)
This study aimed at examining the impact of external debt to the growth and development of capital formation in Nigeria.Time series data was utilized for a period from 1980 to 2013, employing the Autoregressive Distributed Lag (ARDL) modelling. The result of stationarity tests reported a mixed integration at both I(0) and I(1) hence warranting the use of the ARDL.The ARDL estimation also showed the presence of long run relationship amongst the variables.It was also proved that the variables were independently related in the long run. The impact of external debt on capital formation has been established to be negative and statistically significant while savings came out as the only variable with a bidirectional causal relationship amongst the variables. Interest rate was found to be statistically significant even though weak.The other variables were found to be of unidirectional casual effects. Short-run dynamics of the relationship between the variables have also been examined using ARDL error correction modelling. It was established that the disequilibrium in the previous period will be adjusted within the current period by 68 percent showing a speedy adjustment rate.The coefficient of ECM term has the expected sign and significant at one percent. Going by these findings therefore savings should be giving priority and encouraged internally in order to boost the speed of the growth of capital formation in the economy.